Breakthrough Curve Analysis for Fixed-Bed Adsorption of Azo Dyes Using Novel Pine Cone—Derived Active Carbon - Mohammad R. Samarghandi; Mahdi Hadi; Gordon McKay (Adsorption Science & Technology)
A novel activated carbon has been produced from pine cone, a sustainable resource, by phosphoric activation at 900 °C. The BET surface area of the activated carbon was 869 m 2 /g and the methylene blue isotherm area was 734 m 2 /g. The adsorption of two single-component acid azo dyes, Acid Blue 113 (AB113) and Acid Black 1 (AB1), onto this activated carbon was studied using fixed-bed adsorption. Breakthrough curves and equilibrium isotherms were obtained for the adsorption of these two dyes onto the prepared active carbon. The highest adsorption capacities achieved for AB113 and AB1 were 485 and 286 mg dye/g carbon, respectively. Two-column breakthrough curve models were applied to correlate the experimental adsorption breakthrough curves for each dye: the Thomas model, based on solid-phase internal diffusion, has been applied with considerable success; and the saturation isotherm model approach of Michaels was used with a reasonable degree of success.